Wykorzystanie rozwłóknionych odpadów wielowarstwowych laminowanych kartonów do płynnej żywności jako napełniaczy polietylenuThe utilisation of waste of defibered laminated multi-ply boards for liquid food as the fillers for polyethylene - Kowalska, E.; Kuczyńska, L.; Wielgosz, Z.; Choroś, M. (Polimery, 2022)
On the basis of literature data the present possibilities to use the waste of multi-ply board packages for liquid food (e.g. milk or juice) as the source of fiber cellulose fillers for thermoplastic polymers’ composites have been discussed. The own method of such waste defibering was presented (Fig. 4) and its products were used as the fillers in polyethylene composites. The effects of polyethylene type (PE-HD, PE-LD, agglomerate of PE-LD packaging film, PE-LD waste from cable production) and the content of cellulose fibers (up to 48 wt. % what corresponds to 64.5 wt. % of waste boards) on the mechanical properties of the composites (Table 1-5, Fig. 7-13). The composites obtained show significant stiffness and hardness as well as good tensile and acoustic properties and simultaneously esthetic surface view. So they can be applied to produce various objects of daily use (pots, buckets, trashcans, garden furniture etc.).